146 LA cervix care: Improving cervical cancer prevention in Louisiana – Identification of barriers to care for those women at increased risk for cervical dysplasia - Deborah Smith; Deborah G. Smith; Donna Williams; Bilikisu “Reni” Elewonibi; Jennifer E Cameron; Jerry McLarty; Shreveport Michael E Hagensee (Journal of Clinical and Translational Science)
Objectives/Goals: Cervical cancer is preventable through HPV vaccination and the detection/removal of precancerous lesions. Incidence and mortality rates have only decreased by 3–4% in the past decade. Despite having the tools to prevent all cervical cancers, they are not being fully utilized. Our goal is to identify barriers and design strategies to overcome them. Methods/Study Population: Women in urban (750) and rural (750) settings will be screened for the presence of high-oncogenic risk HPV (hrHPV) by self-vaginal swab, complete the Monitoring Blunting Style Scale, a validation scale to determine attentional style, and a structural barrier to care survey. A subset (Results/Anticipated Results: The study, launched in September 2024 at the Medicine Primary Care Clinic at UMC in New Orleans, has enrolled 16 women. Sample adequacy was high (82%), with 5 women having hrHPV present. Participants expressed high satisfaction and acceptance of the self-administered vaginal swab, with most samples demonstrating high quality. Surveys have been collected, and hrHPV-positive women have been referred for gynecological follow-up. Shreveport site will recruit women across over 20 rural clinical sites using a Mobile Health Unit to increase access in rural and underserved communities. Discussion/Significance of Impact: The baseline study will take 12–18 months. We will identify and address key barriers to follow-up gynecological care, including logistical issues (improving access and navigation), educational needs (developing culturally sensitive materials), and emotional support. We will create a care delivery model to eliminate cervical cancer in Louisiana.